Composition and optical properties of chromium oxynitride films. (25th July 2022) - Wang, Jin; Tu, Yuchun; Yuan, Yanyan; Qian, Han; Jonnard, Philippe; Lan, Rui
Abstract : The films with various components were prepared by using the reaction gases N2 and O2 combined with the Cr2 O3 and CrN targets. The focus of this study is at the composition, optical, and bandgap properties of the CrO x N y thin films. X‐ray diffraction, X‐ray photoelectron spectroscopy, and ultraviolet–visible–near‐infrared (UV‐vis‐NIR) spectroscopy were used to investigate the phase structure, chemical composition, and optical properties of the films, respectively. The results show that the films mainly consisted of CrO2 phases. The (O + N)/Cr atomic ratio deduced from X‐ray photoelectron spectroscopy (XPS) in the films prepared with the Cr2 O3 target increased with the increase of nitrogen flow, whereas the nitrogen concentration in samples prepared with the CrN target was greatly affected by O2 gases flow. When the oxygen flow was as low as 1.0 sccm, the sample is mainly composed of oxides. The thin films prepared with the oxide target presented a good transmittance of 60%–80% in the visible range. The bandgap, as obtained using the absorption value, spanned a range of 1.3–2.6 eV. These results provide an excellent suggestion for the preparation of the chromium oxynitrides films applied in the aspect of mechanical, optical and electrical properties.